MODELING OF WIND TURBINE CONTROL SYSTEM AND OPTIMIZATION OF REGULATOR PARAMETERS - Yandylskiy, Olexandre; Marchenko, Anatoliy; Guliy, Volodymyr (Scientific Works of Vinnytsia National Technical University, 2015)
System of linear differential equations for modeling of automatic regulation of angular velocity of wind turbine rotor, taking into account the impact of wind velocity, power of loading and regulation delay time is suggested. Optimization of PID regulator coefficients, using object-oriented library of non-linear systems of Matlab environment which enables to determine the parameters of regulator, that meet the requirements of optimality criterion, is carried out. REFERENCES 1. Кривцов В. С. Невичерпна енергія: підручник. Кн. 2. Вітроенергетика / Кривцов В. С., Олейников А. М., Яковлєв А. І. − Харків: Вид-во Нац. аерокосмічного ун-ту. «ХАІ», Севастополь: Севастополь. нац. техн. ун-т, 2004. − 519 с. 2. Буяльский В. И. К вопросу оценки параметра времени включения двигателя привода питча для ветротурбины USW56−100 / В. И. Буяльский // Вісник СевНТУ Сер. Механіка, енергетика, екологія: зб. наук. пр. − 2010. − Вип. 106. – С. 114 – 119. 3. Резван В. Абсолютная устойчивость автоматических систем с запаздыванием / Резван В.; под. ред. В. А. Якубовича; с доп. А. П. Лихтарникова, В. А. Якубовича. − М.: Наука, 1983. − 256 с. 4. Веремей Е. И. Пособие " Nonlinear Control Design Blockset " [Електронний ресурс] / Е. И. Веремей, С. В. Погожев. − Режим доступу: http://matlab.exponenta.ru/nonlinecondes/book1/preface.php.